Effect of Patient's Knowledge and OHI-S on Periodontal Disease Among Age Group 19–64 Years in the Dental Clinic at the Community Health Centre, Bareng, Malang - Andari Astuti, Indrian; Yunus, Moch; Warih Gayatri, Rara (KnE Life Sciences, 2021)
Periodontal disease, also known as gum disease, is a combination of several inflammatory conditions accumulated from supporting tissues in the teeth that result from bacterial infections. Periodontal disease develop gradually and become increasingly severe, so maintaining good periodontal health is important. The patient’s level of knowledge about periodontal disease can directly affect their periodontal health. It is generally caused by poor oral hygiene. Nevertheless, dental and oral hygiene values can be measured by the Simplified Oral Hygiene Index (OHI-S). This cross-sectional study included patients visiting the Dental Care and Orthodontic Health Clinic at the Community Health Centre in Bareng, Malang, aged between 19 and 64 years. The research instrument used was a questionnaire and patients’ medical records.. The results showed a significant relationship between the level of knowledge and the OHI-S with periodontal disease using the contingency coefficient test, with p-value = 0.026 on the variable level of knowledge and p-value = 0.045 on the OHI-S variable. A significant relationship was also seen between the level of knowledge and periodontal disease (p = 0.026) and between OHI-S and periodontal disease (p = 0.045). Further study of the stronger effect between the two is needed. Keywords: the level of knowledge, Oral Hygiene Index Simplified (OHI-S), periodontal disease